2020
DOI: 10.3892/etm.2020.8899
|View full text |Cite
|
Sign up to set email alerts
|

hsa‑microRNA‑411‑5p regulates proliferation, migration and invasion by targeting the hyaluronan mediated motility receptor in ovarian cancer

Abstract: The mortality rate of ovarian cancer is the highest out of all gynecological malignancies worldwide. Therefore, it is important to understand the mechanisms of ovarian cancer, identify new biomarkers and develop targeted drugs. The role and molecular mechanisms of hsa-microRNA (miR)-411-5p in ovarian cancer have not been fully elucidated. The present study investigated the ovarian cancer cell lines OVCAR-8 and SKOV3. After transfection with miRNA mimics, cell proliferation was monitored by a proliferation assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…16 Growing evidence has indicated that miRNAs can regulate the progression of various cancers by regulating cell growth, migration, invasion, and apoptosis, such as pancreatic cancer, papillary thyroid cancer, and ovarian cancer. [17][18][19] For instance, miR-133a-3p repressed the growth and metastasis of gastric cancer cells via blocking autophagymediated glutaminolysis. 20 MiRNA-106a has been confirmed to promote breast cancer cells' proliferation, clonogenicity, migration, and invasion but inhibit their apoptosis and chemosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…16 Growing evidence has indicated that miRNAs can regulate the progression of various cancers by regulating cell growth, migration, invasion, and apoptosis, such as pancreatic cancer, papillary thyroid cancer, and ovarian cancer. [17][18][19] For instance, miR-133a-3p repressed the growth and metastasis of gastric cancer cells via blocking autophagymediated glutaminolysis. 20 MiRNA-106a has been confirmed to promote breast cancer cells' proliferation, clonogenicity, migration, and invasion but inhibit their apoptosis and chemosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“… 28 HMMR is associated with BC risk and cancer progression across multiple tumor types. 29 , 30 HMMR has been reported to be resistant to chemotherapy by inducing epithelial‐mesenchymal transformation in gastric cancer through the TGFβ/Smad2 pathway. 31 Existing evidence has revealed that HMMR is often freakishly expressed in human tumors and its overexpression might accelerate the formation and progression of different cancers, such as lung adenocarcinoma 32 and colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…HMMR is one of the few defining receptors for hyaluronan and was a centrosomal and microtubule‐associated protein that regulates cell growth 28 . HMMR is associated with BC risk and cancer progression across multiple tumor types 29,30 . HMMR has been reported to be resistant to chemotherapy by inducing epithelial‐mesenchymal transformation in gastric cancer through the TGFβ/Smad2 pathway 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Former researchers have revealed that miR‐411‐5p is able to serve as tumour‐suppressing miRNA in several tumours. For examples, miR‐411‐5p could target HMMR to play a suppressing role in ovarian cancer (He et al, 2020). Moreover, miR‐411‐5p decreased GRB2 to limit breast cancer cell metastasis and proliferation (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%